2015
DOI: 10.1515/anre-2015-0023
|View full text |Cite
|
Sign up to set email alerts
|

Health literacy and health among the elderly: status and challenges in the context of the Polish population aging process

Abstract: Introduction: Poland is a country which is characterized by the process of population aging resulting in a dynamic growth of the old-age dependency ratio. Thus, along with the aging process, we can expect, both at the individual and at the societal level, the intensification of the problems related to coping with worsening health and social dependency of the growing number of the elderly. One of the most necessary action contributing to the prevention of the above-mentioned threats is the development of health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 21 publications
2
7
0
Order By: Relevance
“…In their study, most of the elderly had inadequate health literacy ( 2 ). In the study of Slonska et al, more than half of older people in Poland had low health literacy ( 27 ), and in the study of Smith et al, about half of the elderly had borderline and inadequate health literacy ( 28 ), which is consistent with the findings of the present study. In this study, age, education, and health information seeking were directly correlated with health literacy.…”
Section: Discussionsupporting
confidence: 91%
“…In their study, most of the elderly had inadequate health literacy ( 2 ). In the study of Slonska et al, more than half of older people in Poland had low health literacy ( 27 ), and in the study of Smith et al, about half of the elderly had borderline and inadequate health literacy ( 28 ), which is consistent with the findings of the present study. In this study, age, education, and health information seeking were directly correlated with health literacy.…”
Section: Discussionsupporting
confidence: 91%
“…This is a significantly lower HL than in people under 65 years of age. Research conducted by Słońska et al [ 32 ] indicated that in the group of people over 65 years of age, the percentage of people with insufficient HL was the highest when comparing with younger respondents, and it exceeded 60%. Similarly, in another study that evaluated health literacy according to demographic characteristics of Americans aged 16 and over, the oldest group of adults (65 and over) had the lowest HL levels [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…The HLS-EU survey was conducted in eight European countries in 2011 [ 18 , 37 ]. Consent for the use of the Polish version of the questionnaire was given by the Polish coordinator of HLS-EU, Zofia Słońska [ 32 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Higher health competences can lead to better use of the health care system, and the ability to search, understand, evaluate, and apply information. It was also found that health competences were positively associated with self-rated health status [9,10]. The relationship between health competences and the frequency of doctor visits is still unclear, and the question of the quality of health care provided for patients with different SES in Poland remains open.…”
Section: Introductionmentioning
confidence: 99%